Who let the cats out? A global meta-analysis on risk of parasitic infection in indoor versus outdoor domestic cats (Felis catus). (17th April 2019) - Chalkowski, Kayleigh; Wilson, Alan E.; Lepczyk, Christopher A.; Zohdy, Sarah
Abstract : Parasitic infection risks in domestic animals may increase as a result of outdoor activities, often leading to transmission events to and from owners, other domestic animals and wildlife. Furthermore, outdoor access has not been quantified in domestic animals as a risk factor with respect to latitude or parasite transmission pathway. Cats are an ideal model to test parasitic infection risk in outdoor animals because there have been many studies analysing this risk factor in this species; and there is a useful dichotomy in cat ownership between indoor-only cats and those with outdoor access. Thus, we used meta-analysis to determine whether outdoor access is a significant risk factor for parasitic infection in domestic pet cats across 19 different pathogens including many relevant to human, domestic animal and wildlife health, such as Toxoplasma gondii and Toxocara cati . Cats with outdoor access were 2.77 times more likely to be infected with parasites than indoor-only cats. Furthermore, absolute latitude trended towards significance such that each degree increase in absolute latitude increased infection likelihood by 4%. Thus, restricting outdoor access can reduce the risk of parasitic infection in cats and reduce the risk of zoonotic parasite transmission, spillover to sympatric wildlife and negative impacts on feline health.